The Effects of Mattering and Combat Deployment on Student Service Members/Veterans’ College Adjustment: A Psychosociocultural Approach - Bryan C. Bodrog; Alberta M. Gloria; Dustin Gregory Brockberg (Journal of Veterans Studies, 2018)
This study examined college adjustment for 157 student service members/veterans’ (SSM/V) college adjustment using a psychosociocultural framework to explore psychological (stress), social (connection and university mattering), and cultural (view of self) dimensions. A series of mediation analyses revealed that mattering fully mediated the relationships of social and campus connectedness and negative view of self with college adjustment, respectively. Mattering also partially-mediated the relationship of positive view of self and college adjustment. Although those SSM/V who had been deployed to a combat zone held more negative views of self and reported decreased social connectedness than those who had not, deployment to a combat zone did not moderate the relationships of connection (social and campus) and view of self (positive and negative) with college adjustment. The study’s findings direct student service personnel to provide emic support and programming to support SSM/Vs’ educational experiences and college adjustment.